Analyzing the Neuroprotective Potential of Nicotine in Parkinson’s Disease (PD) and its Effect on Dopamine Levels in Rodents and Primates - Colbourne, Jessica; Lock, Daniella; Buffone, Lucas; Sivaloganathan, Vithurry (Université d'Ottawa | University of Ottawa, 2015)
Parkinson’s Disease (PD) is the second most common neurodegenerative disease. While there is no cure to PD, there are multiple speculated environmental factors that predispose an individual. Recent research suggests that nicotine can serve as a neuroprotective factor in Parkinson’s disease. The aim of this literature review is to determine whether the literature indicates a relationship between the use of nicotine and PD. Keywords "(parkinson’s*) AND (neuroprotection) OR (rats) OR (nicotine) OR (mouse) OR (dopamine)", were searched through University of Ottawa Search+ database.